Russian-Greek Political and Ecclesiastical Relations in 20-30s of the 19th Century - E. P. Kudryavtseva (Vestnik MGIMO-Universiteta)
The article is devoted to the Russian-Greek ecclesiastical and political relations before and during the Eastern Crisis of the 1820s. After the start of the Greek uprising in 1821, Russia took an ambivalent position: as a patron of all orthodox Christians in the Ottoman Empire, it sought to support the Greeks, but Russia also had to recognize the Greek revolution as an illegitimate rebellion. As a member of the Holy Alliance of European Powers Russia had no other choice but to adhere to the principles of legitimism. Russia had both political and economic interests in the region. After the Greek uprising, main powers in the Western Europe had no doubt that Russia would support the rebels. Nevertheless, Russia regarded the Greek rebellion as another European revolution. After a successful war of independence, Russia established its diplomatic mission in the Greek capital. The first ambassador was P.I. Rickman, who arrived with aim to provide political relations with this new Balkan state. If political support of the rebellion could find no understanding in the conservative European circles, the aid of the Orthodox Balkan Church was implied by the Treaty of Küçük Kaynarca 1774. Special attention in this support, provided by the Holy Synod of the Russian Orthodox Church to the Greek monasteries, was paid to the Athos monasteries. This support was designed by a special document. It was adopted in 1735 under the Empress Anna Ivanovna and was subject to execution in subsequent years. The Archive of the Russian Ministry of Foreign Affairs has kept lists of all Orthodox monasteries on the territory of the Ottoman Empire that enjoyed material support from the Russian church; a significant part of this list are the Orthodox churches of Greece.